Efektivitas Unit Pengolahan Air di Depot Air Minum Isi Ulang (DAMIU) Dalam Menurunkan Kadar Logam (Fe, Mn) dan Mikroba di Kota Pekalongan - Saleh, Rosmiati; Setiani, Onny; Nurjazuli, Nurjazuli (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2013)
Background:The number of drinking-water-refill center were increasing only in quantity but not in providing the quality of water. Therefore it takes a special handling and attention, not only because the low-quality of water causing various diseases.The data from the Pekalongan City Health servic showed that only 13 of 55 drinking-water-refill center (24%) which have actively examined their sample water each month in bacteriological test, 3 of them (20%) proved to be unqualified. Furthermore, while for chemical examination, there were only 6 (11%) which actively doing it, and 2 of them (33%) mentioned as unqualified. After doing examination to the raw water, it was found that the content of Fe metal was 2.51 mg/1, Mn metal was 2.41 mg/1, the parameters found was beyond the standard. Methode:The kind of research held was explanatory research using cross sectional design. The sample was taken by proportional sampling. The number of samples was 35 refill centers.The data would be analyzed uding Chi-Square,pairedt-test,Kruskall Wallis, McNemar Test) and multivariate test (Logistc regression). Result:The results of this research showed that 23 samples (66%) had an unqualified Fe metal content with the average content was 0,34 mg/l, 19 samples (54%) had an unqualified Mn metal content, with the average content was 0.47 mg/1, 26 samples (74%) with The unqualified quality of E.coli. The other test carried out in the drinking-water refill, resulted that 25 samples (71%) had a qualified Fe metal content, the average was 0.29/1 and 22 samples (63%) had a qualified E.coli content.The results of Bivariate analysis showed that the condition of raw water, the equipment, the processing, the sanitation, the SOP compliance, significantly related to the decreasing of Fe, Mn metal content and E.coli (p. <0.05). While the results of the multivariate analysis from 5 variables, 1 of which were statistically proven that there was a asosiation relationship between raw water conditions and the decreasing E.coli with p= 0.02 with theOR(95%CI)= 2.238(1.299 - 67.645). The effectiveness of drinking-water-refill center management in reducing the levels of Fe, Mn and E.coli, with Fe, p= 0.00, Mn p= 0.04,E.colip= 0.00. is strongly influenced by the condition of the raw water, the condition of the equipment, and the processing. Keywords : The effectiveness of drinking-water-refill treatment, chemical and bacteriological quality